Characterization of gamma irradiated PUREX solvent – A systematic study. Issue 8 (23rd May 2020) - Mishra, Satyabrata; P, Vishnu Anand; Sridhar, M.; Pandey, N.K.; Sankaran, K.; Joseph, M.
ABSTRACT: Radiolysis products were identified in gamma irradiated PUREX solvent under simulated conditions encountered during reprocessing of fast reactor spent nuclear fuel. The irradiated solvent after alkali wash was fractionally distilled for the ease of their analysis. Spectroscopic analysis of various fractions using techniques like Fourier-transform infrared spectroscopy (FT-IR), gas chromatography, gas chromatography-mass spectrometry (GC-MS), and matrix-assisted laser desorption/ionization (MALDI) revealed formation of various classes of compounds which result from fragmentation as well as recombination. 4-Decanol, 4-dodecanol, and oxalic acid were identified as the diluent degradation products. Metal retention behavior suggested the diluent recovered through distillation can be reused as neat diluent.